POTENSI DAN EKSISTENSI CADANGAN PANGAN MASYARAKAT DI KABUPATEN PATI - Suroso, Suroso (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah (BAPPERIDA) Kabupaten Pati, 2017)
ENGLISHFood reserve is very important to guarantee the fulfilment of the community’s consumption needs. The aim of the research was to analyse the domestic potential, the existing, and the coverage of community food reserve in the study area. This research used quantitative and descriptive approaches. The variables consisted of the potential, the existing, and the coverage of food reserve. Data were collected through interview and survey for the primary data. Meanwhile, the observation on the relevant documents was conducted to obtain the secondary data. Data were analyzed descriptively. The research had 9 findings. Firstly, the average of the domestic potential of the food reserve was 237,030,630.47 kg annually. Secondly, the existing of the food reserve at the licensed institutions was 4,107,861.28 kg. Thirdly, the potential proxy of the food reserve at the unlicensed institutions was 232,996,149.68 kg. Fourthly, the government food reserve was 14,904,773.4 kg. Fifthly, the total of the monthly community food consumption was 9,330,835.50 kg. Sixthly, the coverage of the potential of food reserve was 25.4 months. Seventhly, the coverage for existing of food reserve at the licensed institutions was 0.44 month (13 days). Eighthly, the coverage of the food reserve at the outside of licensed institutions was 24.96 months. Ninthly, the coverage of the government food reserve was 1.597 months (47.92 days). INDONESIACadangan pangan sangat penting untuk menjamin pemenuhan kebutuhan konsumsi pangan masyarakat. Tujuan penelitian adalah untuk menganalisis potensi domestik, eksistensi, dan coverage cadangan pangan masyarakat di lokasi penelitian. Penelitian menggunakan pendekatan deskriptif-kuantitatif. Variabel penelitian meliputi potensi, eksistensi, dan coverage cadangan pangan. Pengumpulan data primer dilakukan dengan menggunakan teknik wawancara dan survei. Sedangkan, observasi dokumen yang relevan dilakukan untuk memperoleh data sekunder. Analisis data dilakukan secara diskriptif. Penelitian ini memiliki 9 temuan. Pertama, rata-rata potensi cadangan pangan di area studi sebanyak 237.030.630,47 kg pertahun. Kedua, eksistensi cadangan pangan milik usaha pangan berijin sebanyak 4.107.861,28 kg. Ketiga, proksi potensi cadangan pangan milik masyarakat umum nonusaha pangan berijin sebesar 232.996.149,68 kg. Keempat, cadangan pangan milik pemerintah yang meliputi lumbung pangan daerah dan BULOG sebanyak 14.904.773,4 kg. Kelima, jumlah konsumsi pangan penduduk perbulan sebanyak 9.330.835,50. Keenam, coverage potensi cadangan pangan domestik sebesar 25,40 bulan (2,12 tahun). Ketujuh, coverage eksistensi cadangan pangan masyarakat pada lembaga berijin sebesar 0,44 bulan (13 hari). Kedelapan, coverage potensi cadangan pangan pada masyarakat umum sebesar 24,96 bulan. Kesembilan, coverage cadangan pangan milik pemerintah sebesar 1,597 bulan (47,92 hari).